Studies on behavior of suspension of silica nanoparticle in aqueous polyacrylamide solution for application in enhanced oil recovery - Maurya, Neetish Kumar; Mandal, Ajay (Petroleum science and technology, 2016)
The use of nanoparticle/polymer suspension for high-temperature and high-saline reservoir was investigated by measuring rheological properties and characterizing the interaction between polymer and nanoparticle. Polyacrylamide (PAM) and silica nanoparticle were used in this study. The result indicates that silica/PAM suspension have higher viscosity and viscosity retention was improved in the presence of salt and at high temperature as compared to simple PAM solution. Improved performance was attributed to the formation of complex macromolecular structure. PAM gets adsorbed on the surface of silica due to hydrogen bonding and the silica particle act as physical cross-linker between polymeric chains, resulting in improvement of viscosity.